A velhice e o envelhecimento do ator: entre o palco e os bastidores - Dias, Ricardo Aparecido (2007)
This essay looks trough the process of how an actor deals with his own oldness, precisely in the city of São Paulo, in between 1948/49/50 by the time theater (TBC ), radio (Tupi / Diffused ), movie (Vera Cruz ) and television (TV Tupi) connection and the 2006. At the first chapter, the reasons take took the author to choose these theme will be exposed, followed by the purpose and the methodology used in the research. At the second chapter, this paper will presents the concepts of Social Gerontology, old age and the process trough an actor deals with his own oldness and performing arts, playwright and languages of performing arts. At the third chapter the chronology of the main artistic and politician facts related to the old actors in São Paulo during the period of the research will be presented. This period of 58 years will be separated in different phases: Performing Arts and the Modernity, Performing Arts as Social Engagement, Resistance at the Censorship and to the Military Regime, Fights for Amnesty and Redemocratization and Performing Arts by the time of early democracy. The purpose of this is to evidence the participation of who nowadays are the old actors focused in this paper and the role played by them in today's at the social questions. The fourth chapter that's a analysis of this chronology , apportioned well into motifs appurtenant to the performing arts and at the old age. At the considerations endings completes as the old actors today's did not can and must not be considered all of equal : than it is to there are several oldness among them. Considers as well than it is to they are not influential merely now and they always have been social acting. Another closure is, in the last 58 years, the old actor left of having chance to work well into the radio soup operas , but , on the other hand , he saw the opening the doors from the television and the one theater best organised in spite of that difficulties as of in case that hold at the occupation ( and as of age into it ) still they may be unlimited.. The labour contains still , as an addendum , a list of the main theatrical spectacles with old actors stars, as of 2001 the one 2006, and also a list of the more important movies played by old actors at the period between 2003 and 2006 with the names of your interpreters